2006
DOI: 10.1152/japplphysiol.00575.2005
|View full text |Cite
|
Sign up to set email alerts
|

Nasal wall compliance in vasomotor rhinitis

Abstract: Nasal compliance is a measure related to the blood volume in the nasal mucosa. The objective of this study was to better understand the vascular response in vasomotor rhinitis by measuring nasal cross-sectional area and nasal compliance before and after mucosal decongestion in 10 patients with vasomotor rhinitis compared with 10 healthy subjects. Nasal compliance was inferred by measuring nasal area by acoustic rhinometry at pressures ranging from atmospheric pressure to a negative pressure of -10 cmH2O. Mucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 22 publications
0
17
0
2
Order By: Relevance
“…A lack of change in nasal compliance after administration of nasal oxymetazoline compared with normal subjects lends support to the hypothesis that vasomotor rhinitis may be attributable to autonomic dysfunction. 758 Rhinitis from food ingestion 22. Rhinitis may occur after ingestion of foods or alcoholic products.…”
Section: Vasomotor Rhinitismentioning
confidence: 99%
“…A lack of change in nasal compliance after administration of nasal oxymetazoline compared with normal subjects lends support to the hypothesis that vasomotor rhinitis may be attributable to autonomic dysfunction. 758 Rhinitis from food ingestion 22. Rhinitis may occur after ingestion of foods or alcoholic products.…”
Section: Vasomotor Rhinitismentioning
confidence: 99%
“…We found that the cross-sectional areas of this plastinated nose model are in the range of the areas of healthy patients with mucosal decongestion obtained by acoustic reflection method. 20 It is hard to pinpoint the exact reason for the relative disagreement observed at the highest values of flow rates between experimental and numerical results except that laminar flow may not be verified throughout the model. Consequently, it was more difficult to achieve convergence for the highest flow rate values.…”
Section: Discussionmentioning
confidence: 96%
“…Eine Eosinophilie spricht gegen das Vorliegen einer vasomotorischen Rhinitis [291] . Diagnostisch unterst ü tzt eine fehlende Ä nderung des nasalen Widerstandes auf Oxymetazolin die Hypothese einer urs ä chlichen autonomen Fehlinnervation [301] und hilft in der individuellen Diagnosestellung. Auch Messungen der Herzfrequenz zeigten eine relative parasympathische Hyperaktivit ä t [302] .…”
Section: Rhinitis Vasomotoricaunclassified